2023
DOI: 10.31127/tuje.1145716
|View full text |Cite
|
Sign up to set email alerts
|

Temperature series analysis of the Hirfanli Dam Basin with the Mann-Kendall and Sequential Mann-Kendall tests

Abstract: The effects of global climate change on hydrological and meteorological variables are increasing day by day. Therefore, hydro-meteorological parameters should be examined carefully. In this study, the effects of global climate change on the Hirfanli Dam Basin temperature series were investigated using the Mann-Kendall Test and Sequential Mann–Kendall Test. The annual mean temperature series of six stations recorded between 1965 and 2017 were analyzed and evaluated. It has been determined that the annual mean t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Additionally, their study revealed that the temperature will rise in the coming years. Also, Zeybekoglu [18] studied the effects of climate change on the Hirfanlı Basin using the M-K test. For this purpose, they evaluated the annual station series between 1965 and 2017 and highlighted that temperatures in the basin have been increasing since the 1990s, which could lead to an increase in the water and meteorological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, their study revealed that the temperature will rise in the coming years. Also, Zeybekoglu [18] studied the effects of climate change on the Hirfanlı Basin using the M-K test. For this purpose, they evaluated the annual station series between 1965 and 2017 and highlighted that temperatures in the basin have been increasing since the 1990s, which could lead to an increase in the water and meteorological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The S-MK test is used to determine if the series is increasing or decreasing with time. While the test displays the data graphically, it also determines the trend's starting point [49]. The t value denotes the test statistic, which was calculated by summing the n i values obtained by counting the smaller ones from the previous ranks for each rank (Equation ( 10)).…”
mentioning
confidence: 99%